If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4 + 2y) = 16 (4 * -2 + 2y * -2) = 16 (-8 + -4y) = 16 Solving -8 + -4y = 16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -4y = 16 + 8 Combine like terms: -8 + 8 = 0 0 + -4y = 16 + 8 -4y = 16 + 8 Combine like terms: 16 + 8 = 24 -4y = 24 Divide each side by '-4'. y = -6 Simplifying y = -6
| Y=-8-76 | | 12+4x+5x^2=0 | | -3.5x=47.25 | | Y=-28-38 | | 4-2=3x+4 | | A=(4x+5)(7x-2) | | -3x+14=3 | | 9(y+3)= | | 2y^2+5y^2-3y^2= | | -12-1y=-15 | | 7x-3x+x-4+5x= | | (6x^5w^2-2xw^6)-(2xw^2)= | | 5b-5-7b-3= | | 4x+24=9x+26 | | -6y-15-7y=-20 | | -6y-15=-20 | | 9t^2+9t-10=0 | | t-46=-30 | | -6y-12+5=-15 | | 9x+3x=y | | 2/5x-6=-16 | | A=(4x+7)(2x+2) | | A=(4x+7)(2x-2) | | y^2+15y-3=0 | | 5y+x+32=5x+y | | A=(4x+7)(2x*2) | | x+-2x=-2 | | 21x^5y-7x^4y^2= | | 12(v+2)-3v=3(3v+1)-8 | | 10x-1=3(3x+2)-5 | | 5x^3-7x^2+8x-7=0 | | A=(9x+5)(4x-7) |